2011
DOI: 10.1097/olq.0b013e3181fe650b
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Syphilis Among Men Who Have Sex With Men—San Diego County, 2004–2009

Abstract: Among 614 men who have sex with men in San Diego County with early syphilis during January 2004 to June 2007, 74 (11.7%; 95% confidence interval: 9.3%-14.4%) had repeat syphilis within 2 years. HIV-infected MSM were more likely to have repeat syphilis (odds ratio: 1.9; 95% confidence interval: 1.1, 3.4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 7 publications
2
26
0
1
Order By: Relevance
“…Follow‐up to ascertain cure and detect reinfection or relapse is achieved by assessing the clinical and serological response to treatment. Globally many studies confirm that follow‐up is poor …”
Section: Managementmentioning
confidence: 99%
“…Follow‐up to ascertain cure and detect reinfection or relapse is achieved by assessing the clinical and serological response to treatment. Globally many studies confirm that follow‐up is poor …”
Section: Managementmentioning
confidence: 99%
“…(iv) Partial immunity. Screening programmes have been taking place in high-risk populations, in which an increasing proportion of syphilis is due to reinfection [15,26]. T. pallidum infection induces partial immunity to reinfection in both humans and other animals, which may lead to an increased proportion of repeat infections being asymptomatic [14,15,24].…”
Section: (I) False-positive Test Resultsmentioning
confidence: 99%
“…A study of MSM from San Diego, California, US, in 2004-07 found no difference [26], whereas other US studies from Florida and Seattle, Washington, in 2000-08 and 1992-2008, respectively, found that persons with repeat syphilis were more likely to present with asymptomatic disease -although in the Florida study this was only statistically significant for the HIV-infected MSM group [9,27]. In the Seattle study, repeat syphilis presented as early latent disease in 113/254 (44.5%) cases, while 309/1,191 (25.9%) cases with initial syphilis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Among men who have sex with men, syphilis is particularly common in those coinfected with HIV and those engaging in sexual behaviors that are associated with a high risk for STDs . And among men who have sex with men, approximately 6–12% of those who have an initial syphilis infection are reinfected within two years . Importantly, those who have repeated syphilis infections are potential core transmitters, because repeated infection suggests continued practice of risky sexual behaviors …”
mentioning
confidence: 99%